Smash that subscribe button! – The evolution of the third-party product reviewer market on YouTube - Murai, Gábor; Kovács, Olivér Béla (Marketing & Menedzsment, 2022)
THE AIM OF THE PAPER In recent years, we could observe a boom in the number of reviewers in the third-party product reviewer market. The structure of this market is an important factor for both firms and consumers as few strong participants could control the narrative around the products. Thus, the main goal of our study is to explore the market structure of this market by shedding light on the drivers behind the growth of the reviewers. METHODOLOGY We collected daily data on English language technology product reviewer channels from YouTube API over a 106-day time window to measure how product reviewers grow over time and estimated hierarchical regression to explore the drivers of the growth process. MOST IMPORTANT RESULTS We found that (1) big channels grow faster, implying a multiplicative growth process, (2) breakthrough videos boost this process, and (3) the audience’s average revealed valence has a significant connection with the subscriber count increase. RECOMMENDATIONS Given the known impact of product reviews on consumers’ decisions, understanding the size and structure of this earned media is key for marketers. Thus, our results and implications are most applicable for firms with products that attract significant demand and supply of product reviews.